A research on critical factors that influence construction productivity related to human power in Gambang and Kuantan - Nurul Anis , Mazni (2013)
Factors affecting the construction productivity are one of the most frequently researched topics in our country. In comparison with rapidly growing economies, we need to increase the productivity level. Our productivity level or output per employee was at 5.8% which is lower than Organisation of Economic Cooperation and Development (OECD) countries. As we know, we need to facing many challenges in order to be a develop nation but the most important is low productivity. The objective of this research is to identify factors that influence the productivity that related to human power, to identify the impact of factor influence to construction productivity and to determine the critical factors that influence the construction productivity related to human power. To achieve this objective, those factors can be identifying through a series of statistical analysis (SPSS) based on collected data of questionnaire survey. From the findings, top ten factor that influenced the productivity were identified such as worker skills, a real construction experience in construction field, change of worker (not loyal to the company), relationship between contractor and worker, communication with foreign worker, worker attitude and morale, labour absenteeism, working overtime, direct supervisor (daily interaction with labourers) and delay in responding to request for information. The most critical factor that influenced the construction productivity related to human power also identified which are worker skills. The result obtain from this research can be used as a guideline in producing the productivity rate which it can help the scheduling of construction production in order to increase our economies.